What Is Political about Jurisprudence? Courts, Politics and Political Science in Europe and the United States - Britta Rehder (Max Planck Institute for the Study of Societies, 2007)
This paper reflects on the literature on courts and politics in Europe and the United States. US-American Political Science has dealt for over fifty years with the role of courts and judges as political actors, whereas this perspective has only recently emerged in Europe. The debates differ not only with regard to the number of articles written, but also with regard to their content. This paper discusses the different research perspectives that are being pursued on both sides of the Atlantic. While a major part of the US-American literature investigates the politics of judicial action and the politicization of the legal system, research on European courts confines itself to analyzing the effects of judicial action, often describing them in terms of juridification. Based on a review of the existing literature, this paper suggests that European scholars ought to take crucial assumptions of the US-American research tradition more seriously. – – Während die US-amerikanische Politikwissenschaft seit über fünfzig Jahren Gerichte als politische Akteure begreift und untersucht, hat sich dieses Verständnis in Europa erst seit Kurzem durchgesetzt. Dabei unterscheiden sich die Forschungsperspektiven erheblich. Ein bedeutender Teil der US-amerikanischen Literatur hat die rechtswissenschaftlichen Ansätze zur Erklärung juristischer Entscheidungen herausgefordert, indem er die politischen Grundlagen der Rechtsprechung und damit die Politisiertheit des Rechtssystems untersucht. Demgegenüber beschränkt sich die europabezogene Forschung meist auf die Analyse der Auswirkungen rechtlichen Handelns auf Politik. Die Effekte werden dabei häufig als Verrechtlichung beschrieben. Der vorliegende Text arbeitet die verschiedenen Forschungstraditionen heraus und plädiert dafür, zentrale Annahmen der USamerikanischen Forschung auch in Europa stärker als bisher zu berücksichtigen.
Keywords: 300; Justiz; Policy-Ansatz; Rechtsprechung; Politikwissenschaft; USA; Europa